Phylogeographic analysis revealed allopatric distribution pattern and biogeographic processes of the widespread pale chub Opsariichthys acutipinnis-evolans complex (Teleostei: Cyprinidae) in southeastern China - Gao, Jiaxin; Yu, Dan; Liu, Huanzhang (Frontiers in Ecology and Evolution, 2023)
Understanding phylogeographic patterns of widespread species can provide insights into their speciation processes and guide the conservation and management measures. In the present study, Cyt b sequences were used to investigate the phylogeographic structure of the Opsariichthys acutipinnis-evolans complex in southeastern China. The gene tree revealed six major lineages (lineage A-F) which were distributed allopatrically, with lineage B distributed in the western part (middle Yangtze and Pearl River) and the other lineages in the eastern part (lower Yangtze and coastal waters of southeastern China). Dating of the lineage diversification revealed the early eastward-westward divergence separating lineage A, B, and C during the late Pliocene and early Pleistocene (3.00, 2.61, and 2.12 Ma, respectively), possibly due to the uplift of the Qinghai-Tibetan Plateau and subsequent orogenies in southeastern China. The following northward-southward diversification resulted in the separation of lineage D, E, and F in the early-middle Pleistocene (1.33 and 0.95 Ma), likely associated with the enhanced succession of glacial cycles during the Early-Middle Pleistocene transition. Although the genetic divergence of 0.017–0.070 among lineages indicated possible different species, morphological characters failed to separate them. Therefore, they were treated as a species complex. Given the distinct genetic divergence of the various lineages, they were suggested as different evolutionary significant units.